Hypothyroidism and Musculoskeletal Injury Susceptibility in Athletes: A Narrative Review - Szkaradowski, Łukasz; Baranowski, Szymon; Lewańska, Julia; Bogdański, Krzysztof; Kruszyńska, Zuzanna; Aleshchyk, Anastasiya; Adamczak, Michał; Majewski, Marcel; Libura, Bogumił; Lazar, Martyna (Quality in Sport, 2026)
Background Thyroid hormones are key elements regulating the body's metabolism, muscle function and connective tissue homeostasis. Therefore, hypothyroidism may affect exercise performance and regeneration processes. Its role as a factor increasing susceptibility to sports injuries remains insufficiently defined. Objective This narrative review aims to evaluate evidence regarding the impact of hypothyroidism on the musculoskeletal system and the risk of sports injuries with attention paid to the underlying physiological mechanisms. Methods Studies published from 1986–2026 were searched in the PubMed database. The literature was reviewed using the following keywords: hypothyroidism, skeletal muscle, tendinopathy, exercise performance, athletes, and musculoskeletal injuries. Additional papers were identified by reviewing references of relevant articles. Results Available evidence indicates that thyroid hormones regulate multiple processes relevant to musculoskeletal health, including oxidative metabolism, neuromuscular function, and extracellular matrix remodeling. Hypothyroidism has been associated with reduced aerobic capacity, impaired muscle strength, and delayed muscle regeneration after injury. Experimental data also suggest disturbances in tendon homeostasis, which may influence tissue adaptation to mechanical loading. Although these findings provide a plausible link between hypothyroidism and increased injury susceptibility, direct evidence in athletic population remains limited. Conclusions Current literature suggests an association between hypothyroidism and impaired musculoskeletal function that may contribute to increased susceptibility to sports-related injuries. Due to the lack of prospective studies in athletes, hypothyroidism should be considered a potential modifying factor rather than a risk factor for injury. Further sport-specific research is required to clarify its significance in injury prevention and athletic management.